On the Problem of Biblical and Liturgical Citation by Mikhail Lomonosov - Matveev, Yevgeniy M. (Slověne = Словѣне. International Journal of Slavic Studies, 2017)
The main objective of this paper is to describe the types and functions of biblical and liturgical citation in M. V. Lomonosov’s works. This research into Lomonosov’s text corpus shows that explicit biblical and liturgical citation can be revealed in the texts of different genres—both in his poetry and in his prose works (and not only in “poetic” rhetorical prose). The paper focuses on different forms of biblical and liturgical contexts in Lomonosov’s panegyric odes, natural science texts, working papers, and letters. Three sources of biblical and liturgical parallels were used: the Moscow Bible (1663), the Festal Menaion (1730), and the Octoechos (1715); the latter includes Lomonosov’s notes in the margins. The research shows that Lomonosov proceeds in various ways: he might mention a Bible source without citation; he might use marked citations; and he might include biblical and liturgical citations into his own speech without reinterpretation, sometimes giving them some additional semantics. Biblical and liturgical phraseology can be described as using the following specific forms: a) phrases that actuate biblical and liturgical semantics in Lomonosov’s panegyric odes (an important issue is to reveal which context is relevant—the biblical or the liturgical); b) those that demonstrate logical consistency between science and religion in Lomonosov’s natural science texts; c) those that construct polemic and ironic context in prose works of different genres; and d) those that emphasize some statements in Lomonosov’s letters, creating the effect of “switching the languages.” Главной задачей настоящей статьи является описание типов и функций библейских и богослужебных цитат в произведениях М. В. Ломоносова. Обращение к корпусу ломоносовских текстов показывает, что явные цитаты из библейских и богослужебных текстов можно найти как в поэзии, так и в прозе, причем не только в “поэтической” ораторской прозе. В статье рассматриваются различные формы использования библейско-богослужебного контекста в торжественных одах, естественнонаучных текстах, служебных документах и письмах Ломоносова. Источниками приводимых в статье библейско-богослужебных цитат послужили Московская Библия (1663), Минея праздничная (1730) и Октоих (1715). Исследование демонстрирует, что в произведениях Ломоносова библейский источник может упоминаться без цитирования, может быть использована маркированная цитата, библейско-богослужебный контекст может включаться в собственную речь Ломоносова без переосмысления, а может приобретать дополнительные смыслы. Особой формой следует считать использование библейско-богослужебной фразеологии. Среди специфических функций библейско-богослужебных заимствований выделяются следующие: а) подключение библейского и богослужебного ассоциативного ряда к сюжету ломоносовской торжественной оды (важной проблемой при этом является определение того, какой именно ассоциативный ряд подключается — собственно библейский или богослужебный); б) иллюстрирование при помощи цитат рассуждения о совместимости науки и религии в естественнонаучных трудах; в) использование библейско-богослужебной речевой стихии для создания полемического и иронического контекста в прозаических произведениях разных жанров; г) акцентирование высказываний в ломоносовских письмах, в результате чего возникает своеобразный эффект “переключения языков”.